Quantifying interaction with robotic toys in pre-term and full-term infants - Kather, Collin; Shofer, Frances S.; Park, Jeong Inn; Bogen, Daniel; Pierce, Samuel R.; Kording, Konrad; Nilan, Kathleen A.; Zhang, Huayan; Prosser, Laura A.; Johnson, Michelle J. (Frontiers in Pediatrics, 2023)
Infants born pre-term are at an increased risk for developmental, behavioral, and motor delay and subsequent disability. When these problems are detected early, clinical intervention can be effective at improving functional outcomes. Current methods of early clinical assessment are resource intensive, require extensive training, and do not always capture infants' behavior in natural play environments. We developed the Play and Neuro Development Assessment (PANDA) Gym, an affordable, mechatronic, sensor-based play environment that can be used outside clinical settings to capture infant visual and motor behavior. Using a set of classification codes developed from the literature, we analyzed videos from 24 pre-term and full-term infants as they played with each of three robotic toys designed to elicit different types of interactions-a lion, an orangutan, and an elephant. We manually coded for frequency and duration of toy interactions such as kicking, grasping, touching, and gazing. Pre-term infants gazed at the toys with similar frequency as full-term infants, but infants born full-term physically engaged more frequently and for longer durations with This is a provisional file, not the final typeset article the robotic toys than infants born pre-term. While we showed we could detect differences between full-term and pre-term infants, further work is needed to determine whether differences see were primarily due to age, developmental delays or a combination.